BAKTERI PENGHASIL AMILASE YANG DIISOLASI DARI EKOENZIM LIMBAH BUAH-BUAHAN - Risky Hadi Wibowo; Welly Darwis; S Sipriyadi; Morina Adfa; Elsi Silvia; Reza Wahyuni; Dhea Amelia Sari; M Masrukhin (Jurnal Biosilampari : Jurnal Biologi, 2022)
Many of potential enzymes can be found in the ecoenzyme, one of them is amylase. Amylase is an enzyme that is able to hydrolize the glycoside bonds of starch or starch into dextrin, glucose and maltose which is widely used in various industries such as beverages. This study aims to isolate the ecoenzyme bacteria and test their ability to produce amylase. Isolation of ecoenzyme bacteria was carried out using serial dilution methods 10-1, 10-3, 10-5. A total of 0.1 ml of each dilution series was pipetted and spread on the Nutrient agar (NA) medium. The bacterial isolates that grew were then purified and identified by morphological observation, Gram staining and their enzymatic activity was tested using Starch Agar (SA) media qualitatively. The results of this study showed there were 39 bacterial isolates from ecoenzyme with different morphological characteristics. The amylase activity test were found that 34 isolates had a positive activity to hydrolize the starch in the SA media which was indicated by the formation of a clear zone around the bacterial colonies. Each bacterial isolate had a different hydrolysis index value, which ranged from 9.45 to 23.65. The highest clear zone diameter index value from starch hydrolysis was EJM 15 isolate.